Alzheimer's Disease and Cancer: Common Targets - Yang, Xueqing; Dai, Jinlian; Wu, Chenglong; Liu, Zongliang (Mini Reviews in Medicinal Chemistry, 2024)
There is growing epidemiologic evidence of an inverse association between cancer and AD. In addition, both cell survival and death are regulated by the same signaling pathways, and their abnormal regulation may be implicated in the occurrence and development of cancer and AD. Research shows that there may be a common molecular mechanism between cancer and AD. This review will discuss the role of GSK3, DAPK1, PP2A, P53 and CB2R in the pathogenesis of cancer and AD and describe the current research status of drug development based on these targets.
Keywords: cancer